The role of K+ channels on spontaneous action potential in rat clonal pituitary GH3 cell line - 임혜원; 백혜정; 호원경; 엄융의 (Eui-Hak Publishing and Printing Co., 2000)
The types of K+ channel which determine the pattern of spontaneous action potential (SAP) were investigated using whole-cell variation of patch clamp techniques under current- and voltage-clamp recording conditions in rat clonal pituitary GH3 cells. Heterogeneous pattern of SAP activities was changed into more regular mode with elongation of activity duration and afterhyperpolarization by treatment of TEA (10 mM). Under this condition, exposure of the class III antiarrhythmic agent E-4031 (5 μM) to GH3 cells hardly affected SAP activities. On the other hand, the main GH3 stimulator thyrotropin-releasing hormone (TRH) still produced its dual effects (transient hyperpolarization and later increase in SAP frequency) in the presence of TEA. However, addition of BaCl2 (2 mM) in the presence of TEA completely blocked SAP repolarization process and produced membrane depolarization in all tested cells. This effect was observed even in TEA- untreated cells and was not mimicked by higher concentration of TEA (30 mM). Also this barium-induced membrane depolarization effect was still observed after L-type Ca2+ channel was blocked by nicardipine (10 μM). These results suggest that barium-sensitive current is important in SAP repolarization process and barium itself may have some depolarizing effect in GH3 cells.